2007
DOI: 10.1590/s1413-35552007000200012
|View full text |Cite
|
Sign up to set email alerts
|

Pain in workers with shoulder impingement syndrome: an assessment using the DASH and McGill pain questionnaires

Abstract: Objective: This study assessed physical function and pain in male and female workers with shoulder impingement syndrome using the Brazilian Portuguese versions of the Disabilities of the Arm, Shoulder and Hand (DASH) and McGill pain questionnaires. Methods: Twenty-seven assembly line workers (18 men and 9 women; mean age of 33.26 ± 6.49 years) in the school supply industry were evaluated. The duration of the shoulder impingement pain was 31.74 ± 32.92 months and the amount of time of the workers in this indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
(26 reference statements)
2
18
0
2
Order By: Relevance
“…Various studies in the literature report that the prevalence of musculoskeletal disorders is greater in women than men [22][23][24][25][26] . It is important to state that women compose the majority of the nursing staff and that this characteristic is due to historical factors 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies in the literature report that the prevalence of musculoskeletal disorders is greater in women than men [22][23][24][25][26] . It is important to state that women compose the majority of the nursing staff and that this characteristic is due to historical factors 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The social division of work left women with activities related to taking care of the sick, children, and the elderly [28][29][30] . Furthermore, the greater incidence of musculoskeletal disorders in women's upper limbs can be due to physiological differences (such as hormonal conditions) or doing chores whilst caring for the family, which requires constant elevation of the arms 22,25,29 . In relation to physical activity, the majority of subjects who participated in this study were sedentary and overweight.…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire was previously used to assess subjects with SIS (Camargo et al 2007;Camargo et al 2009). The DASH self-assessment questionnaire contains 30 questions to measure physical function and symptoms of the upper limbs.…”
Section: Subjectsmentioning
confidence: 99%
“…Several studies have demonstrated the impact of shoulder pain on upper extremity function and health-related quality of life (Camargo et al, 2007). There is evidence suggesting the presence of unilateral regional shoulder mechanical hyperalgesia in these patients (Alburquerque-Sendín et al, 2013), whereas multiregional and bilateral shoulder pain hyperalgesia has been also documented (Hidalgo-Lozano et al, 2010;Paul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%